Absent on Absenteeism: Academic Silence on Student Absenteeism in Canadian Education - Birioukov, Anton (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2021)
Despite mandatory school attendance policies, many students in Canada are frequently absent from school. Absenteeism is linked to numerous negative educational outcomes and is a growing educational issue internationally. This has lead universities in many countries to study the factors associated with absenteeism in order to reduce it. However, the Canadian educational discourse is largely absent on absenteeism. A review of faculty profiles revealed that no Canadian educational scholar investigates absenteeism as their primary area of research. The lack of empirical knowledge concerning student absenteeism is a contributing factor to the high levels of absenteeism evident in Canada. This article serves as a call to action for Canadian academics to research student absenteeism in order to alleviate the behaviour.